2010
DOI: 10.1103/physrevb.81.205105
|View full text |Cite
|
Sign up to set email alerts
|

Electronic collective excitations in compressed lithium fromab initiocalculations: Importance and anisotropy of local-field effects at large momenta

Abstract: According to our ab initio calculations, the recently reported undamped plasmon in compressed fcc lithium emerges not only due to the fact that the dielectric matrix determinant vanishes at long wavelengths at the plasmon energy, i.e., satisfying the ideal condition for an undamped plasmon in a crystal but also extends at large momenta specially along the ⌫L direction. Different from the case of simple metals, the local-field effects dominate, leading to the striking periodicity exhibited by the low-energy pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…The presence of this type of plasmons strongly modifies the reflectivity, leading it to an almost vanishing value close to the plasmon energy. This anomalous optical behavior has been already observed in Na 22 and has been predicted in Li [23][24][25] and AlH 3 . 36 Thus, calcium seems to be another example of this behavior, providing a good example of how pressure-induced complexity is also reflected in the optical properties.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The presence of this type of plasmons strongly modifies the reflectivity, leading it to an almost vanishing value close to the plasmon energy. This anomalous optical behavior has been already observed in Na 22 and has been predicted in Li [23][24][25] and AlH 3 . 36 Thus, calcium seems to be another example of this behavior, providing a good example of how pressure-induced complexity is also reflected in the optical properties.…”
Section: Discussionsupporting
confidence: 78%
“…The inclusion of CLFEs does not significantly modify the plasmon energy position, similar to the interband plasmon found in fcc Li at small momenta. 25 Besides the remarkable low-energy plasmon, higher energy plasmons are also present in the sc phase of Ca. Although at 35 GPa we find two prominent peaks above 10 eV, one at 10.9 eV and the second at 13.1 eV, at the other pressures the second peak is not observed, and only a regular intraband plasmon is present.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence [3][4][5][6][7]9 shows that in the pressure and temperature ranges where the anomalous isotope effect was measured (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) GPa and below 30 K) lithium presents a fcc structure. At around 40 GPa, it transforms to the rhombohedral hR1 phase, which is just a distortion of the fcc phase along the c axis if one switches to a hexagonal representation.…”
Section: Introductionmentioning
confidence: 92%
“…Although it could be expected to evolve to an even more free-electron like system with increasing pressure, it has been shown that pressure not only induces several structural transformations [2,3,4], but also gives rise to a plethora of fascinating physical properties [5] normally induced by nonlocality in the core pseudopotential with pressure [6,7]. For instance, lithium becomes a semiconductor near 80 GPa [8], it melts below ambient temperature (190 K) at around 50 GPa [2] and displays a periodic undamped plasmon according to theoretical calculations [9]. Moreover, it presents one of the highest superconducting critical temperatures (Tc) for an element, reaching values as high as 15 K at around 30 GPa [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%